1988
DOI: 10.1021/bi00425a017
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of a heptadecapeptide comprising the segment encephalitogenic in rhesus monkey

Abstract: The 17-residue peptide FKLGGRDSRSGSPMARR derived from myelin basic protein, containing an epitope encephalitogenic in rhesus monkey, has been studied in aqueous solution by high-resolution one- and two-dimensional carbon and proton nuclear magnetic resonance spectroscopy. The resonances of the spectra from both nuclei were assigned with the aid of two-dimensional correlated spectroscopy, pH and solvent titrations, and one-dimensional spin-decoupling techniques and by comparison of the spectra of the heptadecap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…the rat) and a1 subunit from species known for their sensitivity to the drug (i.e. sheep, human and chicken) clearly indicate that a subunits carry most if not all the ouabain sensitive or resistant phenotype (Price and Lingrel, 1988). Moreover, these experiments indicated that the first half of the molecule, i.e.…”
Section: Introductionmentioning
confidence: 86%
“…the rat) and a1 subunit from species known for their sensitivity to the drug (i.e. sheep, human and chicken) clearly indicate that a subunits carry most if not all the ouabain sensitive or resistant phenotype (Price and Lingrel, 1988). Moreover, these experiments indicated that the first half of the molecule, i.e.…”
Section: Introductionmentioning
confidence: 86%
“…Thirdly, the secondary structure of MBP in aqueous solution is primarily random coil as ascertained by diverse spectroscopic and spectrometric techniques (cited previously), and complexes of the protein with detergents or lipids are too large for effective initial application of traditional solution NMR techniques. Thus, although NMR has provided some local conformational data on MBP or fragments thereof (Mendz and Moore, 1983;Mendz et al, 1986Mendz et al, , 1995aPrice et al, 1988;Tselios et al, 1999Tselios et al, , 2002, modern NMR methodologies have not yet been fully exploited for this protein.…”
Section: Structure Of An Immunodominant Epitope Of Mbp In Situmentioning
confidence: 99%
“…The structural features of the 17-residue epitope of MBP 152-168 (FKLGGRDSRSGSPMARR) have been studied in aqueous solution by high-resolution one-and two-dimensional carbon and proton NMR spectroscopy [217]. Amide proton temperature coefficients, coupling constants, 13 C-spin-lattice relaxation times, and nuclear Overhauser effect data suggested the existence of three structured regions comprising residues 154-157, 158-163 and 163-165.…”
Section: D) Periaxinmentioning
confidence: 99%